Employing non-orthogonal multiple access scheme in UAV-based wireless networks - Do, Dinh-Thuan; Le, Chi-Bao (Bulletin of Electrical Engineering and Informatics, 2021)
This paper studies the two-hop transmission relying unmanned aerial vehicle (UAV) relays which is suitable to implement in the internet of things (IoT) systems. To enhance system performance in order to overcome the large scale fading between the base station (BS) and destination as well as achieve the higher spectrum efficiency, where non-orthogonal multiple access (NOMA) strategies were typically applied for UAV relays to implement massive connections transmission. In particular, outage probability is evaluated via signal to noise ratio (SNR) criterion so that the terminal node can obtain reasonable performance. The derivations and analysis results showed that the considered fixed power allocation scheme provides performance gap among two signals at destination.The numerical simulation confirmed the exactness of derived expressions in the UAV assisted system.